Sensorineural hearing loss in patients with unilateral safe chronic suppurative otitis media - Nanda, Manpreet Singh; Luthra, Dinesh (International Journal of Research in Medical Sciences, 2017)
Background: Chronic Suppurative Otitis Media (CSOM) is the major cause of hearing impairment, mainly conductive type of hearing loss. The occurrence of sensorineural hearing loss (SNHL) in CSOM is controversial and the controversy is more for safe mucosal type. This study aims to assess the association between SNHL and safe mucosal CSOM and its relation to patient’s age, sex, duration of disease, active or inactive disease and speech frequencies. Methods: 100 patients with unilateral mucosal type of CSOM with normal contralateral ear were included in the study. The infected ear was taken as study ear and normal ear as control ear in all patients. All patients underwent hearing assessment by pure tone audiometry for both ears. In case of active disease, ear discharge was first cleared and then audiometric assessment done. Results were statistically compared in all patients for both study and control ears using parameters of patient’s age, sex, duration of disease, speech frequency and active or inactive disease. Results: There was significant higher number of study ears with CSOM having average bone conduction threshold of all frequencies above 25 decibels which implies SNHL (21%) compared to control contralateral ears without infection (5%). There was higher incidence of SNHL at higher speech frequencies. The incidence also increased with age of patient and duration of disease. The incidence was higher in active stage than inactive or quiescent stage. There was no difference among males and females. Conclusion: Safe mucosal CSOM can cause significant SNHL and risk increases with increasing age, duration of disease, higher speech frequencies and presence of active disease.